The impact of a Nickel-Copper smelter on concentrations of toxic elements in local wild food from the Norwegian, Finnish, and Russian border regions - Hansen, Martine Dalgaard; Nøst, Therese Haugdahl; Heimstad, Eldbjørg Sofie; Evenset, Anita; Dudarev, Alexey A.; Rautio, Arja; Myllynen, Päivi; Dushkina, Eugenia V.; Jagodic, Marta; Christensen, Guttorm N.; Anda, Erik Eik; Brustad, Magritt; et al. (International Journal of Environmental Research and Public Health, 2017)
Source at http://dx.doi.org/10.3390/ijerph14070694 Toxic elements emitted from the Pechenganickel complex on the Kola Peninsula have caused concern about potential effects on local wild food in the border regions between Norway, Finland and Russia. The aim of this study was to assess Ni, Cu, Co, As, Pb, Cd, and Hg concentrations in local wild foods from these border regions. During 2013–2014, we collected samples of different berry, mushroom, fish, and game species from sites at varying distances from the Ni-Cu smelter in all three border regions. Our results indicate that the Ni-Cu smelter is the main source of Ni, Co, and As in local wild foods, whereas the sources of Pb and Cd are more complex. We observed no consistent trends for Cu, one of the main toxic elements emitted by the Ni-Cu smelter; nor did we find any trend for Hg in wild food. Concentrations of all investigated toxic elements were highest in mushrooms, except for Hg, which was highest in fish. EU maximum levels of Pb, Cd, and Hg were exceeded in some samples, but most had levels considered safe for human consumption. No international thresholds exist for the other elements under study.